Transient Thermochemical Storage Performance of Methane Reforming in Semi-cavity Reactor Heated by Solar Dish System. (May 2017) - Yuan, Qinyuan; Ding, Jing; Lu, Jianfeng
Abstract: The transient thermochemical storage performance of methane reforming with carbon dioxide in a semi-cavity reactor heat by a dish solar system was numerically investigated. A 3D transient numerical model with Gaussian solar irradiation from dish solar system was proposed to simulate the temperature and species concentration distribution inside the reactor. Along the flow direction, the bed temperature first increases and then decreases, and its maximum appear behind the centre of the reactor. During the starting stage, the bed temperature sharply increases, and the methane mass fraction quickly decreases for the reaction, while the chemical energy storage efficiency and the total energy storage efficiency increase more quickly than the sensible heat energy storage efficiency. When DNI is decreased for a short time, the incident energy flux quickly decreases, while the methane conversion and energy storage change very little, so the energy storage efficiency remarkably increases.